Analysis of Time and Budget Efficiency In The Bungur-Kedoyo Road Project Using Earned Value Method - M. Sulton Bahrudin; Andi Patriadi; Sajiyo Sajiyo (Pelopor Publikasi Akademika, 2025)
The Bungur-Kedoyo road construction project in Tulungagung Regency represents a critical infrastructure initiative aimed at enhancing connectivity and transportation efficiency. However, challenges in managing time and cost effectively remain significant in ensuring project success. This study aims to evaluate the performance of the project using the Earned Value Method (EVM), a comprehensive framework that integrates cost and schedule analysis. EVM metrics, including Schedule Estimate To Completion (SETC), Schedule Estimate At Completion (SEAC), Budget Estimate To Completion (BETC), and Budget Estimate At Completion (BEAC), were employed to monitor and forecast project progress. The findings indicate that the project is largely on schedule, with an estimated additional week required to complete the remaining 96.908% of work, extending the contracted timeline of 180 days slightly. The remaining cost is projected at Rp. 273,570,437.28, and the total expenditure remains below the contract value at Rp. 8,847,685,552.51 out of Rp. 10,640,186,000. These results highlight the effectiveness of EVM in providing precise tracking and forecasting, ensuring the project stays within budget while achieving its objectives. The study concludes that EVM is a valuable tool for managing complex construction projects, offering actionable insights to improve time and cost efficiency for similar future endeavors.